TCF1-positive and TCF1-negative TRM CD8 T cell subsets and cDC1s orchestrate melanoma protection and immunotherapy response - Saraí G De León-Rodríguez; Cristina Aguilar-Flores; Julián A Gajón; Ángel Juárez-Flores; Alejandra Mantilla; Raquel Gerson-Cwilich; José Fabián Martínez-Herrera; Diana Alejandra Villegas-Osorno; Claudia T Gutiérrez-Quiroz; Sergio Buenaventura-Cisneros; Mario Alberto Sánchez-Prieto; Edmundo Castelán-Maldonado; et al. (Journal for ImmunoTherapy of Cancer)
Background Melanoma, the most lethal form of skin cancer, has undergone a transformative treatment shift with the advent of checkpoint blockade immunotherapy (CBI). Understanding the intricate network of immune cells infiltrating the tumor and orchestrating the control of melanoma cells and the response to CBI is currently of utmost importance. There is evidence underscoring the significance of tissue-resident memory (TRM) CD8 T cells and classic dendritic cell type 1 (cDC1) in cancer protection. Transcriptomic studies also support the existence of a TCF7+ (encoding TCF1) T cell as the most important for immunotherapy response, although uncertainty exists about whether there is a TCF1+TRM T cell due to evidence indicating TCF1 downregulation for tissue residency activation.Methods We used multiplexed immunofluorescence and spectral flow cytometry to evaluate TRM CD8 T cells and cDC1 in two melanoma patient cohorts: one immunotherapy-naive and the other receiving immunotherapy. The first cohort was divided between patients free of disease or with metastasis 2 years postdiagnosis while the second between CBI responders and non-responders.Results Our study identifies two CD8+TRM subsets, TCF1+ and TCF1−, correlating with melanoma protection. TCF1+TRM cells show heightened expression of IFN-γ and Ki67 while TCF1− TRM cells exhibit increased expression of cytotoxic molecules. In metastatic patients, TRM subsets undergo a shift in marker expression, with the TCF1− subset displaying increased expression of exhaustion markers. We observed a close spatial correlation between cDC1s and TRMs, with TCF1+TRM/cDC1 pairs enriched in the stroma and TCF1− TRM/cDC1 pairs in tumor areas. Notably, these TCF1− TRMs express cytotoxic molecules and are associated with apoptotic melanoma cells. Both TCF1+ and TCF1− TRM subsets, alongside cDC1, prove relevant to CBI response.Conclusions Our study supports the importance of TRM CD8 T cells and cDC1 in melanoma protection while also highlighting the existence of functionally distinctive TCF1+ and TCF1− TRM subsets, both crucial for melanoma control and CBI response.